ANALISIS MUTU PUPUK ORGANIK LIMBAH BUAH AREN DENGAN BERBAGAI BIOAKTIVATOR: Analysis of the Quality of Palm Fruit Waste Organic Fertilizer with Various Bioactivators - Suparto, Hairu; Rizalli Saidy, Akhmad; Fatimah, Siti (AgriPeat, 2025)
Sugar palm (Arenga pinnata Merr.) is spread quite widely in Indonesia. Most parts of the palm plant have economic value, from the roots, leaves, stems, fruit, to the core of the seeds. Young palm fruit that has been processed is called frond-kaling. Processed fruit from frond-kaling is in great demand. As the demand for palm fruit increases, more and more palm fruit skin waste is produced. Palm fruit skin that accumulates is slow to decompose naturally, this is due to the fairly high lignin content. To speed up decomposition, composting with the addition of bioactivators is an effective solution. This research aims to determine the quality of palm fruit waste compost using various bioactivators with comparisons based on the SNI 19-7030-2004 quality standard. This research was carried out from February to April 2024. This research used descriptive methods, the research consisted of 3 treatments, namely B1 = EM-4 bioactivator, B2 = M-21 bioactivator, B3 = Trichoderma spp bioactivator. The results of the research showed the quality of the waste compost. Palm fruit with EM-4 bioactivator meets SNI 19-7030-2004 except for the C/N ratio variable. The quality of palm fruit waste compost with M-21 bioactivator meets SNI 19-7030-2004 except for the color, pH, C-organic and C/N ratio variables. Quality of palm fruit waste compost with Trichoderma spp bioactivator. meets SNI 19-7030-2004 except for pH variables and C/N ratio